The Effect of Innovation, Market Orientation, and Business Environment Through Competitive Advantages on The Marketing Performance of The Weaving Industry Of Troso in Jepara (Journal of Economic Education, 2022)
A concept used to measure the extent to which a company has achieved as a result of strategic success, which is influenced by innovation, market orientation, business environment and competitive advantage is marketing performance. The purpose of this study was to analyze the effect of innovation, market orientation, and business environment directly and indirectly on marketing performance through competitive advantage and to analyze the effect of competitive advantage on marketing performance. This study was a type of quantitative research using a correlational approach. The population in this study was entrepreneurs of the Troso weaving industry in Jepara. The numbers of samples determined in this study were 90 Small and Medium Industries (IKM). The data collection method was done by using a questionnaire which was tested using validity test, reliability test and classical assumption test. The data analysis techniques in this study were descriptive analysis, path analysis and sobel-test. The results of this study indicated that innovation, market orientation, and business environment have a positive effect on competitive advantage by 5.34%, 24.11% and 3.14%, respectively. Directly, innovation has an effect on marketing performance by 6.35% and indirectly through competitive advantage of 16.47%. Market orientation has a direct effect on marketing performance by 35.88% and has an indirect effect through competitive advantage of 35.01%. The business environment has a direct effect on marketing performance of 0.96% and has an indirect effect through a competitive advantage of 12.62%. Competitive advantage has a positive effect on marketing performance by 50.48%. The most dominant total effect is the market orientation variable of 70.89% and the smallest total effect is the business environment variable of 13.58.